Application of Reliability Prediction Technology in Railway Signal Products - XU Zhengjie (Kongzhi Yu Xinxi Jishu)
As a real time control system to ensure train traffic safety, rail transit signal products must have high reliability and high safety. In order to find out the weak links in the design of rail transit signal products in advance and provide data support for the selection and optimization of product design schemes, this paper takes the switch unit of system security computer platform in railway signaling products as an example to propose a reliability prevention method. At first, reliability block diagram and model are established. Then, the component stress method is used to predict its reliability. At last,according to the comparison between the reliability prediction results and the required reliability indexes, it evaluates whether the design method meets the requirements. The characteristic of this reliability prediction method is that it can make an objective comprehensive evaluation on the reliability level of products under the condition of comprehensively considering various reliability influencing factors. Application results show that the MTBF of the switch unit is 1 005 015 h, and its availability is 99.999 9%.The reliability index meets the specified requirements.